Use of agrochemicals in the seating three pontes, Perolânia (go) Municipality: risk to health factors - Miranda, Celeni (2019)
In this study, a total of forty-three of the twelve settlements were interviewed in the Settlement of Three Bridges, which corresponds to 27.9%. The study also analyzed the use of pesticides in the study area belonging to the municipality of Perolândia (GO), with views to reveal the impacts of these products on public health. The age range of the subjects varies from 35 to 70 years, being able to affirm that it is an adult population. The level of schooling 72.7% is incomplete. Reality that interferes when you think chemicals require a degree of understanding to handle them. For Florêncio et. Al. (2001), "Most workers state that they are not able to understand the instructions and recommendations contained in product labels" (Florêncio, et al. 2001, p. 51). We investigated the use of Personal Protective Equipment (PPE); the knowledge about the agronomic recipe, a mandatory item in the acquisition of these products, and the correct disposal of empty containers. The results showed that of the twelve lots visited 90.9% recognize the importance of the EPis, but they do not use it, all are not aware of the agronomic prescription and 30% outsource the pesticide control of their properties. It is a qualitative research, opting for field study. Data collection instruments were used: the observations, the application of questionnaires and semi-structured interviews. The subjects were the families settled in the Settlement Three Bridges, presenting the reality of this community, about their way of life and mainly the influence of pesticides in their productive activities, as well as their awareness and safety in their use. It was verified that in the researched settlement families use agrochemicals indiscriminately in their crops.